Analisis Pengembangan Sektor Potensial Guna Mendorong Peningkatan Perekonomian Wilayah Kota Kupang Provinsi Nusa Tenggara Timur - M Basri (Jurnal Inovasi Kebijakan, 2020)
Regional development needs to pay attention to regional potential, which can be done by examining the PDRB to see the existence of superior/basic and non-superior/non-basic potential in order to optimize development results to improve welfare. If the government wants its region to develop rapidly, its development program must start from developing superior economic potential. This study aims to analyze the development of potential sectors and formulate alternative strategies for economic development in Kupang City. The analysis method used is Location Quotient (LQ) and SWOT. The results of the study indicate that there are five sectors that have LQ> 1. The most potential sectors to be developed in Kupang City are electricity, gas and clean water; leasing and corporate finance sector, transportation sector; construction sector; and the trade, hotel and restaurant sector. SWOT analysis shows that the factors of Strengths, Weaknesses, Opportunities, and Threats of the potential economic sector development strategy are classified into the Progressive quadrant.